2016
DOI: 10.1097/md.0000000000004878
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging evaluation of acetabular orientation in normal Chinese children

Abstract: There are no data regarding the acetabular orientation on magnetic resonance imaging (MRI); this study investigates the changes of acetabular orientation with age in normal Chinese children.We retrospectively analyzed the medical records of children who underwent hip MRI examination at our hospital from January 2009 to December 2015. A total of 180 patients with normal MRI reading of the hip joints were included and were divided into 14 groups according to age: from 6 months of age and then for each year from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…In a normal newborn, the acetabulum is a cartilage complex composed of acetabular cartilage and Y-shaped cartilage, and the development of the acetabulum is mainly characterized by endochondral ossification after birth. Li et al (2016) measured the OAA and CAA of 180 children with normal hips in different age groups from 6 months to 16 years by using MRI, and found that OAA and CAA were both relatively constant among the different age groups. They speculated that this may be due to the compressive stress of the femoral head on the acetabulum being uniform in the normal hip joint, which tends to balance the growth of the ilium, ischia, and pubis, thereby keeping the acetabulum in a stable axial opening direction.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal newborn, the acetabulum is a cartilage complex composed of acetabular cartilage and Y-shaped cartilage, and the development of the acetabulum is mainly characterized by endochondral ossification after birth. Li et al (2016) measured the OAA and CAA of 180 children with normal hips in different age groups from 6 months to 16 years by using MRI, and found that OAA and CAA were both relatively constant among the different age groups. They speculated that this may be due to the compressive stress of the femoral head on the acetabulum being uniform in the normal hip joint, which tends to balance the growth of the ilium, ischia, and pubis, thereby keeping the acetabulum in a stable axial opening direction.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we used data from slightly older children (aged 3-5 years) to overcome this issue. There have been some reports that pelvic morphology slightly changes between zero and three years of age [ 17 - 19 ], but the morphological change is small. Weiner et al reported that the acetabular anteversion remains almost the same from zero to five years of age [ 18 ], and in the reports of Li et al, it is shown that anteversion and acetabular coverage change only about 1 degree bony from zero to five years of age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports that pelvic morphology slightly changes between zero and three years of age [ 17 - 19 ], but the morphological change is small. Weiner et al reported that the acetabular anteversion remains almost the same from zero to five years of age [ 18 ], and in the reports of Li et al, it is shown that anteversion and acetabular coverage change only about 1 degree bony from zero to five years of age [ 19 ]. Huseynovr et al estimated pelvic morphology from infant to elderly person and stated that pelvic morphology changes little until around age 10, after which it changes significantly for each sex [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al . [40] evaluated the hip morphometry of 180 healthy children of age 1–16 years and did not find any significant gender differences regarding acetabular inclination and Tönnis angle. Comparably, van der List et al .…”
Section: Discussionmentioning
confidence: 99%